Deradikalisasi Pemahaman Keagamaan - Mochammad Achwan Baharuddin (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2019)
This article focuses on the issue of deradicalization of religious understanding through the reinterpretation of the traditions of the Prophet. This focus departs from the phenomenon of fighting in the name of religion or the actualization of the interpretation of religious texts, but the understanding gained is still textually safe. One of them is an understanding of the hadith of heaven under the auspices of the sword. Textually, al-saif is generally interpreted as sharp equipment used in warfare, namely the sword. While al-jannah is generally interpreted as a park or place where Muslims receive gifts from their earthly lives. This study utilizing Jorge J.E Gracia's literature review and interpretation discusses that al-jannah and al-Saif have meanings other than heaven and swords. Al-jannah if transferred proportionally can produce meaning as a vision and mission of life based on love, peace, and peace. While al-saif can be interpreted as patience, stay away from hostility and forgive each other